(untitled) (Kriminalističke teme, 2021)
Implementation of scientific methods in establishing facts relevants for criminalistics and legal proceedings can no longer be imagined without involving forensic examination of biological traces through analysis of DNA molecules. Legal norms for reaching a verdict bases on DNA evidance must be clearly set, and the interpretation and presentation of DNA evidence in court must be improved. Also, judges, prosecutors, lawyers must be constantly acquainted with and educated on the basics of forensics and the use of scientific evidence, in order to properly understand the DNA result and make correct judgments. Missing out some statistic-related facts and probability theory have led to certain legal omissions in both recent and past experience. Our goal with this article is to emphasize the importance of probability theories and statistics in forensic examination, particularly in interpretation of DNA results. Judges and lawyers accept the evidence based on their sense of reasoning. A necessary part is their greater participation and understanding of forensic reports and with the way of interpreting the evidence itself. It is responsibility of lawyers, judges and prosecutors is to understand the statistical evidence as much as possible. Standards of admissibility in court must be legally determined, and statistics and probability theory should be explained in detail to judges so they can make valid judgments.